Against Modernity: the concepts of Emil Staiger, Michail Lifshitz and Hans Sedlmayr. Part 2 - Angelov, Angel (Pitannâ lìteraturoznavstva, 2019)
Objectives of the paper: 1) To analyse Emil Staiger’s theoretical position and to reveal the reason I consider it anti-modern; 2) To compare his position to the one maintained by some ideologists of socialist realism in the same decade, and to outline similarities and differences. I pay more attention to the antimodernist and concept of Michail Al. Lifshitz; 3) To ground my opinion that the ideology of socialist realism in the 1960-ies is also anti-modern; 4) To expand the analysis with a brief introduction of Hans Sedlmayr’s attitude, and to explain why it is anti-modern as well; 5) To give an answer to the question what the social function of the anti-modern attitude is. I use a critical comparative approach to the original sources, asking for the social functions of the analysed concepts. The paper is a part of a monograph in progress on the works of Emil Staiger and on some anti-modern concepts in the reflexion on literature and on visual art in West and in the East of Europe in the 20th century.